2019
DOI: 10.15406/mojwh.2019.08.00225
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of burnout and its associated factors among nurses working in public hospitals of Amhara regional state, Ethiopia

Abstract: Background: Nurses are exposed to professional burnout due to their exposure to physical, mental, and emotional stressors, which can lead to numerous complications in their personal, social, and organizational life. Objectives: To assess the magnitude of nurses' burnout and its associated factors in public hospitals of Amhara regional state, Ethiopia. Methodology: Institutional based cross-sectional study design was conducted on 369 nurses selected by systematic sampling technique. A structured self-administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
2
3
2
1
Order By: Relevance
“…Nurses with fair health status were 13.7 times more risky for burnout than nurses who perceives their health status as good (p-value<0.001). This finding is consistent with the study done in Amhara regional state which revealed increased risk of burnout by perceiving current health status as fair [16].…”
Section: Plos Onesupporting
confidence: 92%
See 4 more Smart Citations
“…Nurses with fair health status were 13.7 times more risky for burnout than nurses who perceives their health status as good (p-value<0.001). This finding is consistent with the study done in Amhara regional state which revealed increased risk of burnout by perceiving current health status as fair [16].…”
Section: Plos Onesupporting
confidence: 92%
“…The nurses who were married were 2.3 times more risky for burnout than nurses who were single (p-value = 0.013). This association was not consistent with the study conducted in Amhara regional state, which showed reduced risk of burnout and married marital status [16]. The difference may due to income levels and other personal characters.…”
Section: Plos Onecontrasting
confidence: 91%
See 3 more Smart Citations